A review of wound healing activity on different wound models - Verma, Renuka; Gupta, Pushpa Prasad; Satapathy, Trilochan; Roy, Amit (Creative Pharma Assent, 2019)
Wound is an injury of living tissue or break in the epithelial integrity of the upper layer of skin. This may lead to disturbance of skin anatomical structure and their function. The normal wounds start to heal immediately after an injury. Normal healing process involved: inflammatory phase, proliferation phase and maturation phase. Now a day wound healing is a challenging clinical problem. So, necessity of effective wound management is required. The various screening models play important role to understand the basic process of tissue repair and treatment of wounds. Wide varieties of in-vitro, ex-vivo and in-vivo models have been developed for evaluation of wound healing activity. The in-vitro models includes Chick chorioallantoic membrane assay, Fibroblast assay, Collagen assay, Scratch assay, Endothelial cell in vitro tube formation assay, Keratinocytes assay. Ex-vivo models includes organotypic culture, human ex vivo skin culture, porcine model, Human organotypic skin explanted culture and the in-vivo models includes Excision wound model, Incision wound Model, Burn wound model, Dead space wound model.The aim of this review article is detailed study of different types of in-vitro, ex-vivo and in-vivo models for evaluation of wound healing activity.